Scholarly publishing initiatives at the International Rice Research Institute: linking users to public goods via open access - Borrero, Albert; Ramos, Mila; Arsenal, Anna; Lopez, Katherine; Hettel, Gene (University of Illinois, 2007)
Scientists at the International Rice Research Institute (IRRI), Philippines, generate a large volume of research results emanating from donor-funded projects. The main objective is to disseminate, as widely as possible, the results of IRRI's research. There is also a strong push to provide free open access to these information resources through modes convenient to researchers in both developing and developed countries. Certain instruments for open access (OA) are already in place at IRRI, including links to full-text publications posted on the Institute's Web site (http://www.irri.org/), especially via the Library branch site (http://ricelib.irri.cgiar.org/), the Rice Knowledge Bank (http://www.knowledgebank.irri.org/), and Rice Publications Archive (http://rice-publications.irri.org/). The joint initiatives of the Library and the Institute's main science publishing units, particularly Communication and Publications Services and the Training Center, typify a convergence of practices to overcome hurdles to OA implementation. This paper explores how the links in IRRI's scholarly publishing chain, bridging information management and publishing, can effectively deliver public goods (knowledge about rice, in this case) to the intended primary users -- researchers and extensionists in the national agricultural research and extension systems (NARES) in developing countries. It also discusses publishing models for delivering public goods generated by an international research organization. To meet its mission, IRRI must employ various demand-supply models to disseminate information. Open access publishing is one model to adopt but first, the onus is on the Institute to overcome issues such as intellectual property rights, funding, and connectivity. IRRI's donors, NARES partners, governments, and rice farmers and consumers expect it to create and share information for the common good, and it strives to convert its resources into electronic format for delivery over the Internet. However, not all its stakeholders are connected. To create impact, IRRI must deliver information through whatever appropriate form, be it cutting-edge digital versions or traditional hard-copy books. This paper discusses this dilemma and hopes to encourage further research and thought on open access publishing.